COLOUR AND ITS EFFECTS ON VOLLEYBALL SERVICE - Virgil Larionescu Moroşan; Florin Vizeteu (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
In this paper we present how the colours and partial occlusion may influence the effectiveness of field service players to perform serve with an upper hand in volleyball. Experiment may notice that the athletes tested had better results in the blue unlike red.